Les surfaces solides : concepts et méthodes - Andrieu, Stéphane (Savoirs actuels. Physique., 2005)
This title gives a large vision of the physics of solid surfaces, from the concepts of basic thermodynamics to that of the surface considered as place of exchange between a crystal and its environment. Exercises of various degrees of complexity are included. This book is aimed at graduate and post-graduate students of physics, engineers or chemistry (condensed materials).